2022
DOI: 10.3389/fnagi.2022.1034542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of sarcopenia without obesity and sarcopenic obesity among Chinese community older people in suburban area of Shanghai: A cross-sectional study

Abstract: ObjectivesThe aim of the present study was to explore the prevalence and risk factors of sarcopenia without obesity (S) and sarcopenic obesity (SO) among community-dwelling older people in the Chongming District of Shanghai, China, according to the Asian Working Group for Sarcopenia (AWGS) 2019 Consensus as the diagnostic criteria of sarcopenia.MethodsIn this cross-sectional study, a total of 1,407 subjects aged ≥65 years were included, where the mean age of the subjects was 71.91 ± 5.59 years and their mean b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Among them, 17 [ 6 , 9 , 13 , 15 , 20 32 ] were cohort studies, and 29 [ 7 8 , 10 , 14 , 17 , 33 56 ] were cross-sectional studies. Articles published in the last 3 years (post-2020) accounted for 28 [ 6 7 , 9 10 , 15 , 20 21 , 23 , 26 31 , 36 , 39 , 41 , 44 47 , 49 50 , 52 56 ] studies. The total number of participants included in this review was 71,757 from studies with sample sizes ranging from 64 [ 34 ] to 7,852 [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, 17 [ 6 , 9 , 13 , 15 , 20 32 ] were cohort studies, and 29 [ 7 8 , 10 , 14 , 17 , 33 56 ] were cross-sectional studies. Articles published in the last 3 years (post-2020) accounted for 28 [ 6 7 , 9 10 , 15 , 20 21 , 23 , 26 31 , 36 , 39 , 41 , 44 47 , 49 50 , 52 56 ] studies. The total number of participants included in this review was 71,757 from studies with sample sizes ranging from 64 [ 34 ] to 7,852 [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies used varying diagnostic criteria for sarcopenia (low muscle mass, low muscle strength, or low muscle strength and mass) combined with different obesity criteria (percentage of body fat [PBF], BMI, or waist circumference [WC]) to diagnose SO. Among them, 14 [ 6 8 , 10 , 13 , 17 , 20 , 22 , 28 , 34 , 45 , 47 , 51 , 54 ] studies used low muscle mass as the diagnostic criterion for sarcopenia, 10 [ 9 , 20 , 26 , 29 , 40 41 , 49 50 , 55 56 ] studies used low muscle strength as the diagnostic criterion for sarcopenia, and 20 [ 14 15 , 21 25 , 27 , 30 31 , 35 36 , 39 , 42 44 , 46 , 48 , 52 53 ] studies used low muscle mass plus low muscle strength as the diagnostic criterion for sarcopenia. In addition, one [ 6 ] study, a multicenter population study, did not provide a specific cutoff for their obesity diagnostic criteria (PBF).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current evidence on the association between sleep duration and the incidence of sarcopenia is inconsistent. For example, several studies have exhibited a U-shaped association between sleep duration and sarcopenia and indicated that both short and long sleep durations were potential risk factors for sarcopenia,6 11 12 while other studies suggested that only short or long sleep duration had a positive association with sarcopenia 13–15. In contrast, studies from China showed that no significant associations were observed between sleep duration and sarcopenia 16 17.…”
Section: Introductionmentioning
confidence: 99%